A new method of muscle strength training by vibrating platform - Wei, X.; Peng, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
A vibrating platform system for muscle strength training has been designed and tested. It is suggested that vibration stimulated strength training is more effectively than the traditional to improve the lower limb strength. The vibrating platform is very useful in muscle strength training.